STRATEGI PROGRAM STUDI AKUNTANSI UNIVERSITAS BUNDA MULIA DALAM MENGHADAPI KONVERGENSI IFRS 2012 - Kurniawati Kurniawati (Jurnal Akuntansi Bisnis, 2017)
The Indonesian Institute of Accountants (IIA) plans to implement the IFRS convergence in 2012 has created a big challenge for several parties, including the accounting education sector in Indonesia. The industry sector hopes that the future accounting graduates will have sufficient knowledge of International Financial Reporting Standards (IFRS). This of course has brought a rather substantial impact for the development of the educational sector in universities, including Bunda Mulia University. This research is a qualitative research that explores which strategies should be used by the Accounting Program at Bunda Mulia University in order to deal with the IFRS convergence 2012, along with the obstacles that the Accounting Program may face with this convergence.To achieve this goal, a questionnaire was distributed and in-depth interviews were conducted to all active accounting lecturers teaching in the odd semester of 2011/2012. The result of this research is expected to give a profile that illustrate the strategies that the Accounting Program at Bunda Mulia University implement to deal with the IFRS convergence 2012.Keywords: IFRS Convergence 2012, Strategy, Accounting Curriculum, International Financial Reporting Standards, IFRS integration.